'J.I. introduces very interesting concepts, but…': From the academic biography of J.I. Ioffe in the late 1930s - V.G. Ananiev (Ученые записки Казанского университета: Серия Гуманитарные науки)
An episode from the academic life of Jeremiah Isaevich Ioffe, an outstanding Russian art historian and cultural theorist, related to the criticism of his book “Music of the Soviet Cinema” (1938–1939) was discussed. The archival materials of the book discussion from the Central State Archive of Literature and Art of St. Petersburg were discussed to answer the question of how J.I. Ioffe’s ideas were perceived by his contemporaries. The institutional context of the discussion is associated with one of the most interesting centers of intellectual life in Leningrad during the 1920s – the Institute of Art History (Zubov Institute), which was called the State Research Institute of Music in the middle of 1930s. It was revealed that J.I. Ioffe maintained professional relationships at the institutional level. His ideas were not rejected completely, and the criticism of the book was rebuffed by the Institute. The situation developed in a different way at the intellectual level. Colleagues showed little interest in J.I. Ioffe’s thoughts. Based on the idea of three types of scientific rationality proposed by V.S. Styopin (classical, non-classical, and post-non-classical), J.I. Ioffe’s research can be attributed to non-classical rationality and the academic mainstream of his times can be associated with classical rationality. The type of system organization of the studied object, the generalized scheme of the method of cognition and the value-target structures of the subject of activity turned out to be different for them. All these differences are clear while analyzing the discussion materials.